Analisa Fundamental Makro dan Struktur Kepemilikan dengan variabel intervening Struktur Modal, Manajemen Laba, dan Kinerja Keuangan yang berpengaruh terhadap Nilai Perusahaan : Studi Kasus: Sub. Sektor Semen yang terdaftar di Bursa Efek Indonesia Tahun 2020-2022 - Veren Putri Shamaya; Hwihanus Hwihanus (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
Developments in the industrial world are currently very rapid, giving rise to tight competition for investors or business actors. As the economy continues to develop, every company wants to demonstrate its best capabilities compared to its competitors, so that to boost operational performance the company requires additional capital. The aim of this research is to find out whether the variables above have an effect on company value. The results of this research are that macro fundamentals, ownership structure, capital structure, earnings management and financial performance have a significant effect on company value.